Multi-Threading and Shared-Memory Pool Techniques for Authorization of Credit Card Systems Using Java - Hamid, Siti Hafizah AB.; Nasir, Mohd Hairul Nizam M.; Ming, Wong Yew; Hassan, Hazrina (INFOCOMP Journal of Computer Science, 2008)
This research paper presents a framework and solution for improving the efficiency of the authorization processing of credit card transactions using multi-threading and shared-memory pool techniques. Through the use of both techniques, a prototype of a real-time multi-threaded authorization system has been developed with Java platforms to overcome the slow sequential authorization processing of a single threaded model of current credit card authorization systems. Via multi-threading technique, it allows parallel execution of the validation functional units involved during the authorization process of credit card transaction through multiple threads. It also enables a separate thread to be executed in the background of the process to perform data synchronization maintained in the shared-memory pool with the main system database. Shared-memory pool has been used to provide a global point of access to the card information kept in the random access memory. During the authorization process, the respective worker thread performs a binary search to obtain the authentication data from the shared memory instead of the system database to hasten the authorization process of credit card transactions. Performancetesting has been carried out to measure the efficiency of a fixed number of credit card authorization processes running between the single-threaded and the multi-threaded authorization systems in a workstation using similar hardware capabilities. Specially-embedded tools are incorporated in the payment gateway applications to obtain the length of end-to-end execution.